Reactive oxygen species production in atmospheric-pressure low-temperature He+O2+H2O plasmas - Kirsty McKay; Felipe Iza; Michael G. Kong (2012)
Low-temperature atmospheric pressure plasmas have received growing interest in recent years, due to their increasing popularity in technological and biological applications. There are many advantages to using these plasmas, for example, they are relatively cheap to run as they do not require expensive vacuum equipment, they are portable, they can be run at near room temperature and they can create complex reactive chemistries inside and outside the discharge region.